Impact of economies of scale in the horticultural sector of the Republic of Moldova - Alexandru Stratan; Victor Moroz; Anatolie Ignat (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The major objective of the article is to provide an overview of the Moldovan High Value Agriculture (HVA) sector that can be useful to investors, producers, traders, donors and government officials alike, enabling concrete actions to be taken toward significantly increasing HVA exports. The article examines how the farm restructuring and land reform processes in Moldova have affected productivity and incomes in horticulture. To capture a comprehensive picture of the impacts of farm restructuring this study integrates analysis into the different quantitative and qualitative surveys during last ten years. The quantitative surveys cover the present situation mostly through questions that can be answered simply through multiple choices of yes/no responses or in a numerical form. The article integrates also the major findings from the Agricultural Census 2011. The qualitative surveys complement the quantitative research by focusing on the process of change involved in restructuring, the reasons for these changes and peoples' attitudes toward the changes. The major conclusion of this paper is that the HVA sector, which used to make a significant contribution to Moldova's economy has undergone a profound collapse which resulted from major structural changes, including the fragmentation of land, depopulation of rural areas ,collapse of most irrigation schemes, and the rapid change in the demand of its traditional destination markets. Faced with this situation it would be unrealistic to expect a rapid recovery of the sector, even though a number of existing private sector initiative demonstrate the potential for profitable investment in a wide range of fresh and partly processed products.
Keywords: 330; Horticulture; structural changes; agricultural policies